COMPOUND SENTENCES IN THE ENGLISH LANGUAGE. ("Conference on Universal Science Research 2023", 2023)
This article gives information about compound sentences in the English language. In this article it has several paragraphs, which give full data about this. It is based on what is sentences? What is the difference between compound and simple sentences? In this article, candidates can learn how to be a good learner and what is compound sentences. And candidates can learn how to use it?